2023
DOI: 10.1083/jcb.202204098
|View full text |Cite
|
Sign up to set email alerts
|

Homophilic interaction of cell adhesion molecule 3 coordinates retina neuroepithelial cell proliferation

Abstract: Correct cell number generation is central to tissue development. However, in vivo roles of coordinated proliferation of individual neural progenitors in regulating cell numbers of developing neural tissues and the underlying molecular mechanism remain mostly elusive. Here, we showed that wild-type (WT) donor retinal progenitor cells (RPCs) generated significantly expanded clones in host retinae with G1-lengthening by p15 (cdkn2a/b) overexpression (p15+) in zebrafish. Further analysis showed that cell adhesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…A recent study showed that Cadm3-mediated homophilic interaction provides an intercellular mechanism underlying coordinated cell proliferation and ensures cell number homeostasis of developing neuroepithelia in zebrafish retina. 46 In mouse retina, Cadm-3-mediated homophilic interaction may also be important in cell proliferation at the early proliferative stage. This evidence supports the symmetric distribution of Necl-1 observed in Necl-1 spots.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that Cadm3-mediated homophilic interaction provides an intercellular mechanism underlying coordinated cell proliferation and ensures cell number homeostasis of developing neuroepithelia in zebrafish retina. 46 In mouse retina, Cadm-3-mediated homophilic interaction may also be important in cell proliferation at the early proliferative stage. This evidence supports the symmetric distribution of Necl-1 observed in Necl-1 spots.…”
Section: Discussionmentioning
confidence: 99%